2016
DOI: 10.1007/s10964-016-0480-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender Moderation of the Intergenerational Transmission and Stability of Depressive Symptoms from Early Adolescence to Early Adulthood

Abstract: Factors that might exacerbate or mitigate the transmission of depressive symptoms from parents to adolescents and the continuity of depressive symptoms into early adulthood are poorly understood. This study tested the hypothesis that the intergenerational transmission and stability of depressive symptoms would be stronger for girls than boys over adolescence and into early adulthood, while considering the possibility that the pattern of gender moderation might vary depending on parent gender and developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 66 publications
(104 reference statements)
1
18
0
1
Order By: Relevance
“…However, these outcomes may be sex-dependent and may vary yet again with the bonding patterns with the male or female parent 63 . Likewise, in a sample of adolescents and their parents in a mainstream population, maternal depressive symptoms predicted increased late adolescent depressive symptoms for girls but not males, whereas paternal depressive symptoms predicted increase depressive symptoms in all youth 64 . There are certainly numerous interacting environmental and biological mechanisms that may be involved in the intergenerational transmission of risk that are involved in these effects, some of which influence males and females similarly and some that do not, and which might differ across the lifespan.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these outcomes may be sex-dependent and may vary yet again with the bonding patterns with the male or female parent 63 . Likewise, in a sample of adolescents and their parents in a mainstream population, maternal depressive symptoms predicted increased late adolescent depressive symptoms for girls but not males, whereas paternal depressive symptoms predicted increase depressive symptoms in all youth 64 . There are certainly numerous interacting environmental and biological mechanisms that may be involved in the intergenerational transmission of risk that are involved in these effects, some of which influence males and females similarly and some that do not, and which might differ across the lifespan.…”
Section: Discussionmentioning
confidence: 98%
“…63 Likewise, in a sample of adolescents and their parents in a mainstream population, maternal depressive symptoms predicted increased late adolescent depressive symptoms for girls but not males, whereas paternal depressive symptoms predicted increase depressive symptoms in all youth. 64 There are certainly numerous interacting environmental and biological mechanisms that may be involved in the intergenerational transmission of risk that are involved in these effects, some of which influence males and females similarly and some that do not, and which might differ across the lifespan. The findings of the present investigation do not speak to the specific mechanisms involved, but they likely reflect the additive or interactive influence of multiple biopsychosocial and cultural factors that remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We also built upon prior research suggesting that a child’s gender moderates intergenerational continuity in depressive symptoms (e.g., Mason et al 2017) and confirmed its importance as the patterns of continuity in depressive symptoms evince varying trends across the gender of offspring. Using contemporaneous measurements of depressive symptoms, the effect of maternal depressive symptoms on sons’ symptoms varies in strength and significance across adolescence whereas the effect of maternal depressive symptoms on daughters’ depressive symptoms is consistently positive and becomes stronger over the course of adolescence.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, intergenerational continuity tends to be stronger among adolescent daughters compared to adolescent sons (e.g., Mason et al 2017; for an exception see Mikkonen et al 2016). Recent research examining the effects of maternal depressive symptoms measured at child age 11 found that maternal depressive symptoms were associated with concurrent depressive symptoms among both sons and daughters, but maternal depressive symptoms assessed at age 11 only predicted depressive symptoms among daughters in late adolescence (age 18; Mason et al 2017). This latter finding highlights two important factors related to intergenerational continuity.…”
Section: Introductionmentioning
confidence: 99%
“…The three most important risk factors for depression in adolescents are female sex, a family history of depression and exposure to psychosocial stress (Thapar et al, 2012). The intergenerational transmission of depressive symptoms arises from a mix of hereditary and environmental factors (Mason et al, 2017;Weissman et al, 2006). Various psychosocial stress factors can induce depression in adolescents (St Clair et al, 2015;Rice et al, 2017), and susceptibility appears to be higher in females than males (St Clair et al, 2015).…”
Section: Introductionmentioning
confidence: 99%